1998
DOI: 10.1007/bf02688660
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a new emotional self-management program on stress, emotions, heart rate variability, DHEA and cortisol

Abstract: This study examined the effects on healthy adults of a new emotional self-management program, consisting of two key techniques, "Cut-Thru" and the "Heart Lock-In." These techniques are designed to eliminate negative thought loops and promote sustained positive emotional states. The hypotheses were that training and practice in these techniques would yield lowered levels of stress and negative emotion and cortisol, while resulting in increased positive emotion and DHEA levels over a one-month period. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 63 publications
4
112
0
4
Order By: Relevance
“…One would typically expect a gradual increase in DHEA after a stress reduction intervention (McCraty et al 1998). The finding that DHEA was decreased in this study sample after the short followup period, combined with the finding that a higher number of officers than would be expected had high baseline levels of cortisol, suggests that these officers are under higher levels of stress than the general population.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…One would typically expect a gradual increase in DHEA after a stress reduction intervention (McCraty et al 1998). The finding that DHEA was decreased in this study sample after the short followup period, combined with the finding that a higher number of officers than would be expected had high baseline levels of cortisol, suggests that these officers are under higher levels of stress than the general population.…”
Section: Discussionmentioning
confidence: 57%
“…These research-based, positive emotion-focused techniques are designed to reduce stress and negative affect, increase positive affect and selfregulation skills, enhance health, and improve cognitive performance (Childre and Cryer 2000;McCraty et al 2006). Previous studies have demonstrated that these techniques favorably impact physiological balance by reducing sympathetic arousal, increasing parasympathetic activity Tiller et al 1996), reducing stress hormone levels (McCraty et al 1998) and enhancing immune system activity Rein et al 1995). These techniques have also been shown to impact organizationally relevant outcomes, such as improving productivity, goal clarity, communication, and job satisfaction, and reducing employee turnover (Barrios-Choplin et al 1997Childre and Cryer 2000;McCraty et al 1991McCraty et al , 2003.…”
Section: Description Of Intervention Programmentioning
confidence: 99%
“…This finding is supported by a research stated that DHEA concentration also increased significantly after resistance training (Copeland et al 2002). DHEA is an ACTH-regulated adrenocortical steroid derived from cholesterol (Kalimi et al 1994) and it can improve psychological wellbeing and its concentration increased significantly with improvement in mental health (McCraty et al 1998). Its concentration is at peak around 20 years old and starts to decrease from the 25 years old.…”
Section: Discussionmentioning
confidence: 68%
“…This is supported by electrophysiological evidence (Bradley et al, 2011). With regular practice, self-regulation of emotions and improved stress responses become increasingly habitual and eventually automatic (McCraty, Barrios-Choplin, Rozman, Atkinson & Watkins, 1998). …”
Section: Ansmentioning
confidence: 99%